2010
DOI: 10.3892/ijmm_00000459
|View full text |Cite
|
Sign up to set email alerts
|

HCC develops even in the early stage of chronic liver disease in elderly patients with HCV infection

Abstract: Abstract. In recent years, the number of elderly patients with hepatocellular carcinoma (HCC) has been increasing. The aim of this study was to compare the liver function and the background factors of HCC patients with hepatitis C virus (HCV) infection by generation and to examine the characteristics of this disease in the elderly. A total of 1096 patients (776 men and 320 women) diagnosed with HCVrelated HCC at our institution from 1995 to 2006 were divided into 4 groups as follows: D group, 75 years of age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They found that HCV-related HCC in patients older than 75 years occurred in mild hepatic inflammation with a slight elevation of ALT, higher serum albuminemia, normal international normalized ratio and mild fibrosis [76].…”
Section: Do the Biochemical Hepatic Markers Correlate With The Develomentioning
confidence: 99%
“…They found that HCV-related HCC in patients older than 75 years occurred in mild hepatic inflammation with a slight elevation of ALT, higher serum albuminemia, normal international normalized ratio and mild fibrosis [76].…”
Section: Do the Biochemical Hepatic Markers Correlate With The Develomentioning
confidence: 99%